Proactive Management that Affects the Efficiency of Credit Management of Bank for Agriculture and Agricultural Cooperatives in the Northeas - ชุมประสงค์ อรอุมา; พงศ์ศาสตร์ การุณ (Journal of Roi Et Rajabhat University, 2019)
This research aimed to 1) study opinions and relationships of proactive management with the efficiency of credit management of the bank for Agriculture and Agricultural Cooperatives in the Northeast. And 2) study proactive management affecting the efficiency of credit management of the bank for Agriculture and Agricultural Cooperatives in the Northeast. The samples were 190 branch managers of the bank for Agriculture and Agricultural Cooperatives in the Northeast. The questionnaire was used for data collection. Quantitative data analysis used descriptive statistics which were mean and standard deviation. Inferential statistics were Pearson’s correlation coefficient and multiple regression. The results showed that branch managers of the bank for Agriculture and Agricultural Cooperatives in the Northeast had an opinion about proactive management and the efficiency of credit management in overall and individual aspect were at high level. A high positive relationship between proactive management and efficiency of credit management. And a proactive management in structure, system, style, staff, and skill had positive affecting to efficiency of credit management of the bank for Agriculture and Agricultural Cooperatives. Therefore, branch managers in the Northeast are able to use working process by applying principle of 7’s McKinsey for proactive management to increase the efficiency of credit management to increase efficiency of credit management of organizations.